FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yap, Veronica; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2024)
This research aims to obtain empirical evidence and analyze the effect of current ratio, total asset turnover, firm size and debt to asset ratio on profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. This study used purposive sampling methods so that 50 companies were obtained. In 50 companies, there are extreme values in the data so that outlier tests are carried out. A total of 8 companies were disposed of, so the samples used were 42 companies. The data collection technique used is secondary data collected and calculated using Microsoft Excel 2016 and processed using the SPSS program version 24. The results of this study showed that the variables current ratio, total asset turnover, and firm size have a positive and significant influence on profitability, while the variable debt to asset ratio has a significant but negative value on profitability. The implication of this research is that companies must pay attention to debt to asset ratio in order to maximize the profitability of the company.